Hepatitis C virus infection status among drug users in Baoshan District - CHEN Jianshuang, ZHU Liming, LE Boxin, WANG Chengyi, LIU Xiaofeng, HE Fan (预防医学)
Objective: To investigate the prevalence and influencing factors of hepatitis C virus (HCV) infection among drug users in Baoshan District, Shanghai Municipality, so as to provide insights into strengthening HCV intervention among drug users. Methods: Drug users under community management in Baoshan District from 2017 to 2023 were recruited. Demographic information, drug use behaviors, sexual behaviors and receipt of intervention service were collected through questionnaire surveys. Blood samples were collected for HCV antibody testing, and the prevalence of anti-HCV antibody was analyzed. Factors affecting the prevalence of anti-HCV antibody among drug users were analyzed using a multivariable logistic regression model. Results: A total of 2 801 drug users were surveyed, including 2 233 males (79.72%) and 568 females (20.28%). The majority of drug users were aged 40 to <60 years (1 663 drug users, 59.37%). The prevalence of anti-HCV antibody was 28.35%, showing an overall upward trend from 2017 to 2023 (P<0.05). Multivariable logistic regression analysis showed that females (OR=1.468, 95%CI: 1.169-1.844), 40 years and over (40 to <50 years, OR=2.441, 95%CI: 1.838-3.242; 50 to <60 years, OR=2.377, 95%CI: 1.787-3.161; 60 to 97 years, OR=1.637, 95%CI: 1.163-2.304), using traditional drugs (OR=2.488, 95%CI: 1.967-3.147) or mixed drugs (OR=2.950, 95%CI: 1.974-4.409), having injected drugs (not share needles, OR=3.649, 95%CI: 2.849-4.673; share needles, OR=3.532, 95%CI: 1.851-6.738) and never using condoms during sexual contacts with spouses/cohabitants in the past year (OR=1.975, 95%CI: 1.354-2.879) were associated with a higher prevalence of anti-HCV antibody; the educational level of high school/technical secondary school (OR=0.483, 95%CI: 0.280-0.835) or college and above (OR=0.280, 95%CI: 0.129-0.608) was associated with a lower prevalence of anti-HCV antibody. Conclusions: The prevalence of anti-HCV antibody among drug users in Baoshan District showed an upward trend from 2017 to 2023. Gender, age, educational level, type of drugs, history of drug injection and never using condoms during sexual contacts with spouses/cohabitants were influencing factors for prevalence of anti-HCV antibody among drug users.